2019
DOI: 10.3390/cancers11040500
|View full text |Cite
|
Sign up to set email alerts
|

Why Has Breast Cancer Screening Failed to Decrease the Incidence of de Novo Stage IV Disease?

Abstract: : Background: Despite screening mammography, the incidence of Stage IV breast cancer (BC) at diagnosis has not decreased over the past four decades. We previously found that many BCs are small due to favorable biology rather than early detection. This study compared the biology of Stage IV cancers with that of small cancers typically found by screening. Methods: Trends in the incidence of localized, regional, and distant female BC were compared using SEER*Stat. The National Cancer Database (NCDB) was then quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
1
20
2
Order By: Relevance
“…Breast cancer is the most common tumors in women and is also a leading cause of cancer-related death worldwide [ 1 ]. About 5–10% of patients with breast cancer are diagnosed with de novo stage IV cancer [ 2 ]. The traditional treatment strategy for these patients is usually based on systemic therapy alone, such as chemotherapy (CTx), hormonal therapy, and/or targeted therapy, while surgery or radiotherapy (RT) are used to palliate the symptoms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common tumors in women and is also a leading cause of cancer-related death worldwide [ 1 ]. About 5–10% of patients with breast cancer are diagnosed with de novo stage IV cancer [ 2 ]. The traditional treatment strategy for these patients is usually based on systemic therapy alone, such as chemotherapy (CTx), hormonal therapy, and/or targeted therapy, while surgery or radiotherapy (RT) are used to palliate the symptoms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One recent study notes that, despite improvements in screening, the nationwide incidence of stage IV breast cancer has not decreased over the last 40 years. 15 This study demonstrates that impoverished, young, and black patients are more likely to present with stage IV breast cancer, often as a consequence of aggressive tumor biology. 15 Moreover, they point out that biologically aggressive tumors demonstrate different growth patterns and physical characteristics, which may complicate their diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…15 This study demonstrates that impoverished, young, and black patients are more likely to present with stage IV breast cancer, often as a consequence of aggressive tumor biology. 15 Moreover, they point out that biologically aggressive tumors demonstrate different growth patterns and physical characteristics, which may complicate their diagnosis. 15 Significantly, the Ohio Medicaid data 16 demonstrate that many of the patients newly covered under Medicaid expansion are those who carry a disproportionately high risk of presenting with stage IV breast cancer.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…There are two studies on screening. Heller looked at approximately 993,000 individuals using a national database, aiming to see why screening did not appear to decrease the incidence of stage IV breast cancer [3]. They found that among those diagnosed up front with stage IV disease, 37.6% had aggressive tumours as compared to 5.1% in those with stage 1 disease, suggesting that the two groups are from different populations with different tumour phenotypes.…”
mentioning
confidence: 99%